Sistem Informasi Objek Parawisata Kalimantan Tengah Berbasis Website - Pranatawijaya, Viktor Handrianus; Pratama, Ferdha Alif (Universitas Palangka Raya, 2022)
Lack of adequate information about tourist objects in Central Kalimantan makes these attractions less well known by the public and tourists so that visitor interest is also reduced. Therefore, these problems need to be overcome by promoting and providing information using website-based information media. The design of this website-based information system aims to promote Central Kalimantan tourism objects that can be accessed anywhere and anytime. A website-based information system is a media that can display elements such as text, animated images and sound so as to make this media interesting. The results of the design of this website-based tourism information system are expected to be able to become a medium that can promote and introduce to the wider community about Central Kalimantan tourism objects so that it can be useful for the government and local communities.